Monitoring the adaptive cell response to hyperosmotic stress by organic devices. (8th May 2017) - D'Angelo, Pasquale; Tarabella, Giuseppe; Romeo, Agostino; Giodice, Angela; Marasso, Simone; Cocuzza, Matteo; Ravanetti, Francesca; Cacchioli, Antonio; Petronini, Pier Giorgio; Iannotta, Salvatore
Abstract: Abstract : Cellular activity upon osmotic stress is related to the occurrence of several disease conditions. The real-time monitoring of the cell response to this kind of stress can give insight into the comprehension of mechanisms involved in cellular shrinkage. Currently the dynamics of the osmotic stress is studied using dedicated and tricky methodologies, not suited to the in vivo testing. We show that a disposable electronic device is very effective for studying the early stage of the osmotic stress induced on human lung adenocarcinoma cells, A549, by a hyperosmotic environment. Our findings corroborate the experimental results obtained by a standard complementary analysis.